Aplikasi Panduan Wisata dan Toko Oleh-Oleh di Provinsi Lampung Menggunakan Google Street View dan Game Engine - Amik Herningsih; A. Ferico Octaviansyah Pasaribu; Yuri Rahmanto (Journal of Data Science and Information Systems, 2023)
Seeing the pandemic that is starting to end and also the ability of Lampung Province to deal with the Covid-19 Pandemic as evidenced by the achievement of the INDONESIA'S BEST PANDEMIC HANDLING award at the 2021 Tribune Lampung Awards, Lampung Province must be able to solve the problems that have arisen from this pandemic. The Lampung Provincial Government (pemrov) said through their official website (lampungprov.go.id) that the Provincial Government will develop various tourism potentials that are expected to support regional development and income. However, tourist centers are not spared by souvenirs that will be brought back by local tourists to their areas. Although tourist attractions are expected to develop the area, souvenir centers are also very influential as regional income. Then created an information media that can show souvenir centers and also tourist centers that are packaged attractively using Google maps and HTML5-based Game Engine as tour guides for a better development and economy of Lampung. This application with Google Streetview can run well on an iframe from the html5 media game engine, using blackbox it can be proven that existing websites can run well without significant problems. Then the test was carried out using ISO 25010 so that it resulted from the Functionality aspect with very good results, namely with a percentage of 87.2%, from the Efficiency aspect with very good results, namely with a percentage of 85.6% and from the usability aspect with very good results, namely with percentage of 86.3%. Then from the results of the PIECES analysis, it was concluded that the menu structure contained in the application can provide convenience in its use.